MENENTUKAN TINGKAT PROFITABILITAS DARI ASPEK LIKUIDITAS DAN SOLVABILITAS - Suhayati, Ely (Jurnal Riset Akuntansi, 2021)
The increase in short-term debt and loans in "the greenback" form to telecommunications companies resulted in reduced profits for a company. The purpose of this study is to determine profitability level from a liquidity and solvency aspects on telecommunications sub-sector service companies listed on the Indonesia Stock Exchange for a period 2015-2019. The method used in this research is descriptive and verification methods, with research object, namely Telecommunication Sub-Sector Service Companies listed on the Indonesia Stock Exchange. The population in this study consisted of 6 telecommunications companies with annual financial reports for the last 5 years. The data were analyzed using multiple linear regression models using SPSS version 25 software. The results showed that influenced profitability by liquidity aspect had a positive effect, while the profitability which was influenced by solvency aspect had a negative effect. This influence shows a different direction a expectations, meaning that telecommunications companies that are good at managing short-term and long-term debt will increase company profit will get. Keywords: Liquidity, Solvency, Profitability